‘I Am That I Am’ and divine titles: A Reformed theological critique - Mudau, Ndidzulafhi (Verbum et ecclesia, 2025)
The heavenly title ‘I Am That I Am’ (Ex 3:14) signifies God’s self-existence and transcendence, which are essential to biblical theology and Christ’s ‘I am’ declarations in the Gospel of John. Modern pastors increasingly employ the phrase and other divine names for self-identification, dangerously overstepping theological boundaries. This pastoral appropriation creates substantial theological dilemmas: it endangers Christ’s singular mediatorial function, cultivates unbiblical spiritual hierarchies, blurs the Creator-creature distinction, and facilitates spiritual abuse by allowing leaders to claim divine authority without accountability. This article analyses the pastoral appropriation of divine titles via the Reformation’s Solus Christus premise, defining the boundaries of pastoral identity and recognising possible consequences. The study examines biblical passages regarding God’s self-revelation and pastoral functions, Reformation writings related to Solus Christus and ecclesiastical authority, and modern sermons that exemplify pastoral divine self-alignment. Exegetical research uncovers significant theological disparities between pastoral divine terminology and Reformed doctrines. ‘I Am That I Am’ refers solely to Yahweh. Reformation theology, which includes Luther’s concept of the priesthood of all believers and Calvin’s view of the ministerial office, rejected clerical claims of ontological distinctiveness. The contemporary pastoral association with the divine undermines Solus Christus and establishes an unbiblical hierarchy, reviving tendencies that reformers condemned. This technique conceals Christ’s sufficiency and may tether consciences to human rather than divine authority. Authentic Reformation healing upholds Christ’s exclusive mediation while seeing pastoral authority as functional and derived.Intradisciplinary and/or interdisciplinary implicationsThe manner in which pastors utilise names for God significantly diverges from the teachings of the Reformation, reflecting a misinterpretation of God’s self-revelation and the appropriate duty of a pastor as delineated in the Bible and theology. This practice reinstates hierarchical inclinations that Reformers criticised, obscures the sufficiency of Christ and may bind consciences to human rather than divine authority. Genuine Reformation recovery maintains Christ’s exclusive mediation while recognising pastoral authority as both functional and derived. This research examines contemporary church leadership through the lens of Reformation principles, elucidating disputes regarding ecclesiastical power and demonstrating the influence of theological shifts on the church’s vitality.